Reference range of glycated hemoglobin in the diagnosis of diabetes mellitus - Badyal, Ashima; Bhatia, Amarjeet S. (International Journal of Research in Medical Sciences, 2017)
Background: Diabetes mellitus is now affecting many in the workforce; it has major and deleterious impact on both individual and national productivity. Glycated hemoglobin (HbA1C) can be used as diagnostic test for diabetes subject to stringent quality assurance tests, while assays are standardized to a criteria aligned to the international reference values. HbA1C has now been recommended by American Diabetic Association (ADA) as a tool to diagnose diabetes. The main objective of the present research is to establish the reference range for glycated hemoglobin in healthy non-diabetic subjects in our hospital laboratory and compare it with the values reported by standard laboratories. Methods: The study was conducted in the Department of Biochemistry, Super Specialty Hospital, Government Medical College, Jammu. Total number of subjects was 50 (25 males, 25 females), aged between 30-70 years. 2ml of venous blood was collected from antecubital vein under aseptic conditions from each individual and put in EDTA vials and the samples were estimated in fully auto-analyzer. Results: This study has delivered different results for males and females. In males, the normal levels were 6.12± 0.76% while in females; the levels were 6.30 ± 0.62%. The overall range in males was 4.3- 7.18% while in females it was 4.7 - 7.30%. Conclusions: The values were comparable (p>0.05) with those reported by standard laboratories, e.g. Dr. Lal Path Labs (<6%) and SRL Lab (≤5.7%). Hence, our values are suitable to be used as cut-off while interpreting the results of patients with diabetes mellitus.